Free reserves and the money supply - Meigs, A. James (Chicago : University of Chicago Press, 1962)
This book is to develop a way to incorporate variation in excess reserve and borrowings, or in a two as combined in free reserve, in a theory of money-supply determination. It employed the analysis of combined elements from the work of Riefler, Currie, Hardy, Turner among others
Issued in microfilm form in 1960 as thesis, Columbia University.
Includes index.
Includes bibliography p. 111-115
usc 21/09/18
Loans
Keywords: Bank reserves; Federal Reserve banks; Money supply